PENERAPAN JUSTICE COLLABORATOR DALAM REPOSISI PENEGAKAN HUKUM INDONESIA PADA KASUS PERSEKONGKOLAN GABUNGAN TENDER - Muhamad Yasirni Bilhikam Ardani (Jurnal Privat Law, 2024)
This article discusses law enforcement challenges related to joint tender conspiracies. The number of tender conspiracy instances has not decreased because to law enforcement deficiencies. Thus, a justice collaborator is required to provide conspiracy case facts. Law enforcement improves in the case. This article addresses problem formulation. First, how is Indonesian joint tender conspiracy law enforcement developing? Second, how do justice collaborators reorient law enforcement in joint tender conspiracy cases? To answer research problems, the author combines doctrinal legal research with a statutory and conceptual approach. This journal article discusses law enforcement evolution in joint tender conspiracy instances and justice collaborators' role in repositioning law enforcement. This second topic will cover the justice collaborator mechanism and game theory in economics. This article suggests that it helps justice collaborators identify joint tender conspiracy occurrences in the KPPU Assembly, simplifying law enforcement and enabling the commission assembly reach the fairest result.